Increased Number of Mast Cells in Epicardial Adipose Tissue of Cardiac Surgery Patients With Coronary Artery Disease - Rozsívalová, Karolína; Pierzynová, Aneta; Kratochvílová, Helena; Lindner, Jaroslav; Lipš, Michal; Kotulák, Tomáš; Ivák, Peter; Netuka, Ivan; Haluzík, Martin; Kučera, Tomáš (Physiological research, 2020)
Chronic inflammation of adipose tissue is associated with the pathogenesis of cardiovascular diseases. Mast cells represent an important component of the innate defense system of the organism. In our work, we quantified mast cell number in epicardial adipose tissue (EAT), subcutaneous adipose tissue (SAT), and right atrial myocardium (RA) in patients undergoing open heart surgery (n=57). Bioptic samples of EAT (n=44), SAT (n=42) and RA (n=17) were fixed by 4 % paraformaldehyde and embedded into paraffin. An anti-mast cell tryptase antibody was used for immunohistochemical detection and quantification of mast cells. We also demonstrated immunohistochemically the expression of CD117 and chymase markers. In EAT of patients with coronary artery disease (CAD), higher incidence of mast cells has been found compared to patients without CAD (3.7±2.6 vs. 2.1±1.2 cells/mm(2)). In SAT and RA, there was no difference in the number of mast cells in CAD and non-CAD patients. Mast cells in SAT, EAT and RA expressed CD117 and chymase. An increased incidence of mast cells in EAT of CAD patients may indicate the specific role of these inflammatory cells in relation to EAT and coronary arteries affected by atherosclerosis.
Keywords: dospělí; mastocyty; Mast Cells; zánět; Female; biologické markery; Cardiac Surgical Procedures; Biomarkers; perikard; Adult; ženské pohlaví; lidé; kardiochirurgické výkony; Aged, 80 and over; Inflammation; Humans; nemoci koronárních tepen; Male; Aged; Coronary Artery Disease; Pericardium; lidé středního věku; senioři nad 80 let; senioři; tuková tkáň; mužské pohlaví; Myocardium; myokard; Middle Aged; Adipose Tissue